2022
DOI: 10.57238/jbb.2022.20107
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effect of Onion‘s Infusion and Garlic‘s Infusion on Escherichia Coli Isolated from Urine Samples

Abstract: Introduction many searchers studies properties ofOnion extract and garlic extract, but they do not study infusion effect of garlic and onion against bacteriaThe Aim to know antibacterial activity of Onion's Infusion and Garlic's Infusion Methodology searcher prepared garlic infusion for many periods, and onion infusion for many periods also, and study antibacterial activity against Escherichia Coli Isolated from Urine Samples Results : thirty urine samples were collected to detect the presence of E. coli and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…To this end, scientists are seeking novel methods to impede the growth of P. aeruginosa biofilms ( Lou et al, 2015 ). The utilization of natural compounds as novel and efficacious medicines has acquired a prominent position in clinical therapies ( Al-khazraji et al, 2022 ; Alarkwazi et al, 2022 ; Hossain et al, 2022 ; Salman, 2022 ). Research has demonstrated that plant-derived substances, such as essential oils (EOs), extracts, and pure chemicals, have notable impacts on bacteria that are resistant to treatment and capable of producing biofilms ( Ahmad et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, scientists are seeking novel methods to impede the growth of P. aeruginosa biofilms ( Lou et al, 2015 ). The utilization of natural compounds as novel and efficacious medicines has acquired a prominent position in clinical therapies ( Al-khazraji et al, 2022 ; Alarkwazi et al, 2022 ; Hossain et al, 2022 ; Salman, 2022 ). Research has demonstrated that plant-derived substances, such as essential oils (EOs), extracts, and pure chemicals, have notable impacts on bacteria that are resistant to treatment and capable of producing biofilms ( Ahmad et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%